(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the experience of countries that have a significant natural potential and pursue an active policy on planning, regulation, support, promotion and monitoring of ecotourism. During the study the methods of formal-logical, comparative and institutional analysis. It is shown that the experience in the development of ecotourism accumulated by different countries testifies to both the specifics of each of the countries and the general approaches, harmonies worshiped with international recommendations and tasks to create conditions for sustainable development of tourism. System approaches existing in different countries and advanced solutions can be recommended in the format of the “right solution”, since they demonstrate how ecotourism can contribute to the achievement of sustainable goals development.